Intimate Relationship Status Variations in Violence Against Women: Urban, Suburban, and Rural Differences. (November 2013) - Rennison, Callie Marie; DeKeseredy, Walter S.; Dragiewicz, Molly
Woman abuse varies across intimate relationship categories (e.g., marriage, divorce, separation). However, it is unclear whether relationship status variations in violence against women differ across urban, suburban, and rural areas. We test the hypothesis that rural females, regardless of their intimate partner relationship status, are at higher risk of intimate violence than their urban and suburban counterparts. Results indicate that marital status is an important aspect of the relationship between intimate victimization and geographic area and that rural divorced and separated females are victimized at rates exceeding their urban counterparts.